Peran Nabi Muhammad sebagai Guru: Role Model dan Motivator - Astuti, Dewi; Hasibuan, Nurainun (Ahdāf: Jurnal Pendidikan Agama Islam, 2023)
This study delineates the role of Prophet Muhammad as a teacher and the significance of educators in education based on both Hadiths and the Qur'an. Employing a library research approach, this study gathered data from various pertinent sources, including classical and contemporary literature, relevant Hadiths, and academic research. By amalgamating information from diverse and credible sources, this research endeavors to provide a comprehensive understanding of Prophet Muhammad's stature as an educator and his role.The findings elucidate that Prophet Muhammad was not solely a prophet and messenger but also a teacher who played a pivotal role in shaping the character, values, and ethics of the Islamic community. He provided tangible examples of righteous living and motivated individuals to pursue knowledge. The study draws vital lessons regarding the role of educators in Islam, the paramount importance of knowledge and education, and the significance of emulating Prophet Muhammad as an exceptional teacher.This research furnishes a deeper comprehension of his contributions to shaping Islamic values and propelling the community towards continuous learning and teaching.